Evolution of CDK1 Paralog Specializations in a Lineage With Fast Developing Planktonic Embryos - Ma, Xiaofei; Øvrebø, Jan Inge; Thompson, Eric M. (Frontiers in Cell and Developmental Biology, 2022)
Abstract The active site of the essential CDK1 kinase is generated by core structural elements, among which the PSTAIRE motif in the critical C-helix, is universally conserved in the single CDK1 ortholog of all metazoans. We report serial CDK1 duplications in the chordate, Oikopleura. Paralog diversifications in the PSTAIRE, activation loop substrate binding platform, ATP entrance site, hinge region, and main Cyclin binding interface, have undergone positive selection to subdivide ancestral CDK1 functions along the S-M phase cell cycle axis. Apparent coevolution of an exclusive CDK1d:Cyclin Ba/b pairing is required for oogenic meiosis and early embryogenesis, a period during which, unusually, CDK1d, rather than Cyclin Ba/b levels, oscillate, to drive very rapid cell cycles. Strikingly, the modified PSTAIRE of odCDK1d shows convergence over great evolutionary distance with plant CDKB, and in both cases, these variants exhibit increased specialization to M-phase.